Prevalence of refractive error in paediatric age group in a tertiary eye center in Onitsha, south east, Nigeria - Ubah, John C; Onyenemezu, Kelechi R; Ikwuka, Obinna V; Okeke, Chukwuemelie D (International Journal of Medical and Health Sciences Research, 2023)
Paediatric ophthalmology is an emerging subspecialty in Nigeria and there is a paucity of data on refractive errors in the country. This study set out to determine the prevalence, type, and factors affecting refractive error among paediatric patients at Guinness Eye Centre, Nnamdi Azikiwe University Teaching Hospital (NAUTH), Onitsha. A retrospective cross-sectional study of 685 patients seen over a 3-year period using the simple random sampling technique. Collected data was analysed using the Statistical Package for the Social Sciences (SPSS) version 20. Of the 685 patients, 242 cases of refractive error were identified giving a prevalence rate of 35.3% with 66.5% of them being female and 33.5% males. The mean age range was 12.0 +/- 3.7 years. Prevalence increased with age from 1.7% among those 0-4 years to 46.3% among those 10-14 years. Myopia was the commonest type of refractive error (62%) while hyperopia was 22.7%. However, there was no case of astigmatism. Poor distant vision was the commonest presenting complaint (34.4%). There is a high risk for refractive error among children with eye complaints and females have a significantly higher proportion. It may be necessary to assess if the male children tend to shy away from complaining of any visual disturbance. Children with refractive errors may not be identified soon enough, and this could account for poor learning in childhood. So, children should be routinely screened for refractive error.